Influence of Synthesis Time on the Morphology and Properties of CeO2 Nanoparticles: An Experimental-Theoretical Study - Oliveira, Regiane Cristina de [UNESP]; Ciola Amoresi, Rafael Aparecido [UNESP]; Marana, Naiara Leticia [UNESP]; Zaghete, Maria Aparecida [UNESP]; Ponce, Miguel; Chiquito, Adenilson Jose; Sambrano, Julio Ricardo [UNESP]; Longo, Elson; Simoes, Alexandre Zirpoli [UNESP] (Amer Chemical Soc, 2020)
Here we combined experimental and theoretical results to correlate the morphological, optical, and electronic properties of cerium oxide (CeO2) prepared by a microwave-assisted hydrothermal method with varying synthesis times. X-ray diffraction confirmed a cubic structure without deleterious phases. Density functional theory simulations confirmed an indirect (K-L) bandgap energy of 2.80 eV, with an electron transition between O-2p and Ce-4f orbitals, which agrees with the value obtained using diffuse reflectance. Raman spectroscopy shows that changing the synthesis times results in samples with different defect densities at a short range. Theoretical calculations confirmed that the deformations and changes in the experimental Raman spectra area result in oxygen displacement; as the displacement decreases, the crystallinity increases, and only one peak was observed. Scanning electron microscopy and high-resolution transmission electron microscopy show changes in the morphologies as the synthesis time varies. For shorter times, sheet and polyhedral morphologies were noted. With time increases, the sheets turn into nanorods and nanowires until the nanowires decrease and cubes are observed. In addition, an initial study regarding the influence of the surface on the electric response of CeO2 was completed. It was observed that the presence of different surface defects ([CeO6 center dot 2V(o)(x)] or [CeO7 center dot V-o(x)]) can alter the material resistance.